Comorbidity of allergic rhinitis and asthma in children - N. A. Ivanova (Медицинский совет, 2014)
Allergic rhinitis (AR) and bronchial asthma (BA) are certainly interrelated. Understanding the mechanisms of the relation could contribute to timely diagnosis and more effective treatment of both AP and AD in case of combination.